2019
DOI: 10.4028/www.scientific.net/kem.801.331
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polysulfone/Organomontmorillonite Blends on Nanocomposite Membrane Properties

Abstract: In this study, an organically modified montmorillonite (OMMT) hydrophilic clay was incorporated in PSf through non-solvent induced phase separation fabrication process to improve its properties. Afterwards, hand casting was done and the PSf/OMMT membranes produced were characterized to determine the effect of OMMT addition to its structural, mechanical and thermal properties, and hydrophilicity. Scanning electron microscope (SEM) images of the surfaces showed a denser surface as the OMMT content increases but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
2
1
0
Order By: Relevance
“…Furthermore, glass transition temperatures (Tg) for PSU film were found at 189.15 °C. This value was in concordance with those reported elsewhere (190–200 °C) [ 66 , 67 , 68 ]. Sequentially, PSU-VIM membranes displayed a Tg range of 185.40 to 186.58 °C.…”
Section: Resultssupporting
confidence: 94%
“…Furthermore, glass transition temperatures (Tg) for PSU film were found at 189.15 °C. This value was in concordance with those reported elsewhere (190–200 °C) [ 66 , 67 , 68 ]. Sequentially, PSU-VIM membranes displayed a Tg range of 185.40 to 186.58 °C.…”
Section: Resultssupporting
confidence: 94%
“…Figure 5a indicates that glass transition temperature ( T g ) of the PSF membrane was 182.71°C. This value was close to that (190–200°C) of most literatures 29,32,33 . The literature reported that the T g value of the PSF membrane was 142°C 34 .…”
Section: Resultssupporting
confidence: 87%
“…close to that (190-200 C) of most literatures. 29,32,33 The literature reported that the T g value of the PSF membrane was 142 C. 34 The T g value of the CM-PSF membrane decreased to 173 C, and the T g value of the T-PSF membrane further decreased to 158.24 C. This phenomenon was reported in literature 27 : The T g value of CM-PSF decreased from 183 to 158 C, which depended on the grafting degree. Higher grafting degree resulted in lower glass transition temperature.…”
Section: Thermal Behavior Of the Membranesmentioning
confidence: 68%